Declaration of "outstanding Universal Value" and the commodification of the image of a city - Cristina Mattiucci (lo Squaderno, 2016)
The historic center of Naples has been placed in the list of the UNESCO World Heritage since 1995. Its candidature is synthetized in the record n. 726, where the area, its boundaries and its features are describes, as well as the reasons to consider it of "Outstanding Universal Value":"Naples is one of the most ancient cities in Europe, whose contemporary urban fabric preserves the elements of its long and eventful history. Its street pattern, its wealth of historic buildings from many periods, and its setting on the Bay of Naples give it an outstanding universal value without parallel, and one that has had a profound influence in many parts of Europe and beyond".